Oral health status and treatment needs of female beedi factory workers in Mangalore city, India - Vanishree N; Peter S. Sequeira; Ashwini Rao; Nishi Gupta; Chandrashekar B.S; Mohan A.N.J (Al Ameen Medical College, 2014)
Purpose: To determine oral health status and treatment needs of female beedi factory workers in Mangalore city, Karnataka. Methods: A cross-sectional study was conducted on 426 female beedi factory workers age 15-70 years in Mangalore city to find out their oral health status and treatment needs. Data collection was done on a structured proforma: regarding demographic data, oral hygiene habits, personal habits, past dental history and data on oral health status and treatment needs was recorded using WHO oral health assessment form (1997). Results: Out of 418 dentate patients only 2 (0.47%) had healthy periodontium, 68 (16.26%) and 348 (83.25%) had gingival disease and periodontal disease respectively. Healthy periodontium and bleeding was seen only in younger age groups (15-24 years and 25-34 years), whereas as age increased score of code 4 (Deep pockets) also increased. The prevalence of dental caries was found to be 82.6%. The total mean DMFT was 5.97±5.78. The mean DT was 4.06±4.03, mean MT was 1.88±3.71 and mean FT was 0.03±0.20. Of the total study population 46 subjects exhibited oral lesions. Conclusions: There are more proportions of unfulfilled treatment needs in this working class as they are not provided with dental treatment, appropriate public health actions at various levels need to be taken like health education and health promotion to curtail the disease in this population.